Literacy-Based Islamic Cultural History Learning at Islamic Elementary School - Nurotul Faidah; Muhammad Anas Maarif (Program Pascasarjana Universitas Ibrahimy, 2022)
The purpose of this article is to discuss the planning, implementation, and evaluation of literacy-based Islamic Cultural History learning at Madrash Ibtidaiyah/ Islamic Elementary School (MI) Tarbiyatul Ulum Pengampon Menganti Gresik. This article uses qualitative research with a case study approach. Sources of data are obtained from primary data and secondary data. Data collection techniques are observation, interviews, and documentation. Data analysis techniques are data reduction, data presentation, and verification/drawing conclusions. While the data validity technique uses the criteria of credibility, transferability, dependability, and confirmability. The results of this study are literacy-based Islamic Cultural History learning at MI Tarbiyatul Ulum Pengampon Menganti Gresik carried out in three stages, 1) Planning in the form of making Learning Implementation Plans tailored to student needs, 2) Learning implementation which is divided into three stages namely preliminary activities, core activities, and closing activities. In the core activities using various literacy-based methods and media, namely Lecture, Mind Mapping, Audio Visual and Reading Corner, 3) Learning evaluation is carried out covering three domains, namely affective, cognitive and psychomotor.